2016
DOI: 10.1038/srep25671
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationship between Schizophrenia and Nicotine Dependence

Abstract: It is well known that most schizophrenia patients smoke cigarettes. There are different hypotheses postulating the underlying mechanisms of this comorbidity. We used summary statistics from large meta-analyses of plasma cotinine concentration (COT), Fagerström test for nicotine dependence (FTND) and schizophrenia to examine the genetic relationship between these traits. We found that schizophrenia risk scores calculated at P-value thresholds of 5 × 10−3 and larger predicted FTND and cigarettes smoked per day (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 76 publications
(97 reference statements)
5
51
1
1
Order By: Relevance
“…In general, the associations became stronger overall with less restrictive p-value cutoffs, which is consistent with previous studies (22, 23). In the mega-analysis, the association between any substance use disorder and schizophrenia polygenic risk score peaked at p T <0.5; pseudo R 2 range 0.8% to 3.7%, minimum p = 4×10 −23 .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In general, the associations became stronger overall with less restrictive p-value cutoffs, which is consistent with previous studies (22, 23). In the mega-analysis, the association between any substance use disorder and schizophrenia polygenic risk score peaked at p T <0.5; pseudo R 2 range 0.8% to 3.7%, minimum p = 4×10 −23 .…”
Section: Resultssupporting
confidence: 92%
“…Our data suggest that when testing the relationship between a substance-related phenotype and the polygenic risk score for schizophrenia, the diagnosis of any substance use disorder may be the most informative substance-related phenotype to use, especially with a heterogeneously ascertained series of samples. Despite this, we would expect that analyses with large enough sample sizes, as in the study reported by Chen et al (22), will detect attenuated associations between the schizophrenia polygenic risk score and individual substance use disorder. These findings highlight the power of carefully ascertained smaller samples where precise phenotyping can provide useful insights (and large effect sizes) that may not otherwise be seen.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, a recent US study suggests that smoking rates have declined significantly less among adults with mental illness than those without 36. Similarly, our findings suggest that public health efforts to reduce smoking in the general population may not have been as effective for those with schizophrenia who may require more targeted clinical interventions, especially given that schizophrenia itself may be associated biologically with an increased risk for nicotine dependence 37. Focused interventions and prevention strategies to target obesity and smoking in high-risk groups, such as those with serious mental illness, are therefore warranted.…”
Section: Discussionmentioning
confidence: 53%